Morphologically Controlled Efficient Air‐Processed Organic Solar Cells from Halogen‐Free Solvent System. Issue 7 (29th December 2022) - Rasool, Shafket; Kim, Jae Won; Cho, Hye Won; Kim, Ye‐Jin; Lee, Dong Chan; Park, Chan Beom; Lee, Woojin; Kwon, Oh‐Hoon; Cho, Shinuk; Kim, Jin Young
Abstract: Power conversion efficiencies (PCEs) of glove‐box (GB) processed, two‐component, single‐junction organic solar cells (OSCs) have recently exceeded 18%. However, their mass‐scale manufacture using roll‐to‐roll (R2R) coating techniques is impracticable if they must be fabricated in an air‐free environment. From a commercialization perspective, efficient air‐processed OSCs are of much greater interest than GB‐processed devices since the vast majority of R2R‐manufacturing infrastructure is designed to operate in the air. Herein, it is reported that controlling the crystallinity of non‐fullerene acceptors plays a key role in determining the properties of blend films. Notably, Y6‐hu (a Y6‐derivative) is shown to exhibits a higher degree of crystallinity when processed in air. Air‐processed OSCs show an outstanding PCE of 17.38%, which, to the best of the authors' knowledge, is the highest PCE yet reported for two‐component‐based OSCs processed in air using halogen‐free solvents. Moreover, opaque large‐area OSC sub‐modules with PCEs of 12.44%, and red‐green‐blue colored semi‐transparent OSC sub‐modules with PCEs of >10% are demonstrated. By understanding how morphological features relate to the charge‐generation dynamics of air‐processed OSCs, a new window is opened for the fabrication of efficient and stable air‐processable organic electronics. Abstract : Fabricating efficient air‐processed organic solar cells (OSCs) using green‐solvents and the simplest possible photoactive material‐combinations is vital for their commercial viability, since roll‐to‐roll‐processing infrastructure is designed to operate in ambient‐conditions. In this article, air‐processed OSCs are reported that show enhanced crystallinity and long‐lived charge‐separated states, resulting in 17.38% power conversion efficiency in a two‐component and green‐solvent‐based OSC‐system which is higher than its glove‐box processed counterpart.